2020
DOI: 10.1515/cclm-2020-1366
|View full text |Cite
|
Sign up to set email alerts
|

Non-HDL-C/TG ratio indicates significant underestimation of calculated low-density lipoprotein cholesterol (LDL-C) better than TG level: a study on the reliability of mathematical formulas used for LDL-C estimation

Abstract: Objectives Low-density lipoprotein cholesterol (LDL-C) is the main laboratory parameter used for the management of cardiovascular disease. The aim of this study was to compare measured LDL-C with LDL-C as calculated by the Friedewald, Martin/Hopkins, Vujovic, and Sampson formulas with regard to triglyceride (TG), LDL-C and non-high-density lipoprotein cholesterol (non-HDL-C)/TG ratio. Methods The 1,209 calculated LDL-C result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0
4

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 23 publications
1
8
0
4
Order By: Relevance
“…15,16 Entretanto, esses estudos não compararam a precisão dessas equações em relação a um método de referência. Mais recentemente, Cwiklinska et al, 17 associados usaram tanto β-quantificação e um ensaio de LDL direto para comparar as equações de Martin/Hopkins e Sampson, e eles relataram que ambos os métodos eram mais precisos que a equação de Friedewald. 17 Embora esse estudo não tenha oferecido uma comparação direta entre as duas novas equações, seus números indicam que o número de casos acima da meta de total de erros de 12% foi menor com a equação de Martin/Hopkins (134 vs. 157 casos).…”
Section: Discussionunclassified
See 3 more Smart Citations
“…15,16 Entretanto, esses estudos não compararam a precisão dessas equações em relação a um método de referência. Mais recentemente, Cwiklinska et al, 17 associados usaram tanto β-quantificação e um ensaio de LDL direto para comparar as equações de Martin/Hopkins e Sampson, e eles relataram que ambos os métodos eram mais precisos que a equação de Friedewald. 17 Embora esse estudo não tenha oferecido uma comparação direta entre as duas novas equações, seus números indicam que o número de casos acima da meta de total de erros de 12% foi menor com a equação de Martin/Hopkins (134 vs. 157 casos).…”
Section: Discussionunclassified
“…Mais recentemente, Cwiklinska et al, 17 associados usaram tanto β-quantificação e um ensaio de LDL direto para comparar as equações de Martin/Hopkins e Sampson, e eles relataram que ambos os métodos eram mais precisos que a equação de Friedewald. 17 Embora esse estudo não tenha oferecido uma comparação direta entre as duas novas equações, seus números indicam que o número de casos acima da meta de total de erros de 12% foi menor com a equação de Martin/Hopkins (134 vs. 157 casos). 17 No entanto, esse estudo não relatou a possível importância clínica desses achados, e estes não foram específicos para pacientes com diabetes.…”
Section: Discussionunclassified
See 2 more Smart Citations
“…Hypercholesterolemia is an independent risk factor for coronary heart disease (CHD) and LDL-C is the principal laboratory parameter used for CVD management [ 12 ]. The experts of the National Lipid Association concluded that increased non-HDL-C and LDL-C levels were the root causes of atherosclerosis because they are involved in the majority of clinical CHD events [ 13 , 14 ].…”
Section: Discussionmentioning
confidence: 99%